The never-ending Kashmir dispute and its implications on the contemporary global governance and peace - al-Ahsan, Abdullah (International Islamic University Malaysia, 2017)
The Kashmir dispute is one of the oldest unresolved conflicts in theannals of the United Nations. India has concealed its duplicitybehind “democracy” in this dispute. As a result of the romanticfascination for his ancestral land, the first Indian Prime Minister,Jawaharlal Nehru, wanted to retain Kashmir as a part of India whichturned out to be one of the deadliest international conflicts of the 20thcentury. On the surface Nehru wanted to demonstrate India’s “secular” character by incorporating Muslim-majority Kashmir intoIndia. The Delhi administration has consistently manipulated thisdispute in India’s favor through political, diplomatic, emotional andintellectual means and has successfully used the media andthink-tanks to solicit support for it. Pakistan, on the other hand,although initially committed to the idea of self-determination for thepeople of Kashmir, has been inconsistent and undiplomatic insupporting the cause. Clandestine agencies have created groupsamong Kashmiri people, and occasionally made them fight againstone another. The conflict in neighboring Afghanistan contributedto the deteriorating situation in Kashmir. Overall, Kashmir hasbecome a source of constant intimidation within the Muslim societytoday.